2023
DOI: 10.1007/s11060-023-04248-z
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent efficacy of bevacizumab in recurrent glioblastoma

Abstract: BackgroundBevacizumab (BEV), at a standard dose of 10 mg/kg every 2 weeks is associated with prolonged progression-free survival (PFS) but no improvement in overall survival (OS) in recurrent glioblastoma (rGBM). Few studies have examined the potential dose-dependent e cacy of BEV. In Ontario, reimbursement for the costs of BEV varies, and as a result, our practice began to routinely use lower dose regimens. The main aim of this study was to ensure that there was no harm to patients who received the low dose p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that antiangiogenic agents have an inhibitory effect on glioblastoma ( 11 ). For the treatment of glioblastoma, BEV can bind to its blood circulation target, change the kinetic relationship between ligand binding to endothelial cells and down-regulate angiogenic signals, so as to achieve the purpose of inhibiting tumor growth ( 12 ). Therefore, BEV is a relatively suitable drug for glioma treatment in combination with TMZ.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that antiangiogenic agents have an inhibitory effect on glioblastoma ( 11 ). For the treatment of glioblastoma, BEV can bind to its blood circulation target, change the kinetic relationship between ligand binding to endothelial cells and down-regulate angiogenic signals, so as to achieve the purpose of inhibiting tumor growth ( 12 ). Therefore, BEV is a relatively suitable drug for glioma treatment in combination with TMZ.…”
Section: Introductionmentioning
confidence: 99%